2021
DOI: 10.1177/00034894211015590
|View full text |Cite
|
Sign up to set email alerts
|

Peritonsillar Abscess Size as a Predictor of Medical Therapy Success

Abstract: Objective: To evaluate the success of sole medical therapy (MT) versus surgical therapy (ST) in patients with both clinically and radiographically confirmed peritonsillar abscess (PTA). To also determine treatment safety based on abscess size, and identify predictors of treatment failure. Methods: This was a retrospective cohort of 3 hospitals in a single academic health system. A total of 214 immunocompetent patients diagnosed with uncomplicated PTA underwent a contrasted CT scan of the neck. About 87 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We did not specifically assess the effect of ultrasound on the patient's clinical management or clinical course. However, some studies have demonstrated relatively high success with the conservative management of PTA using IV antibiotics and corticosteroids, comparable to surgical intervention 34,35 . Conservative management seems to be more successful in smaller PTAs 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not specifically assess the effect of ultrasound on the patient's clinical management or clinical course. However, some studies have demonstrated relatively high success with the conservative management of PTA using IV antibiotics and corticosteroids, comparable to surgical intervention 34,35 . Conservative management seems to be more successful in smaller PTAs 35 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated relatively high success with the conservative management of PTA using IV antibiotics and corticosteroids, comparable to surgical intervention. 34,35 Conservative management seems to be more successful in smaller PTAs. 35 Given this, the diagnostic test characteristics of ultrasound for PTA may be sufficiently acceptable for diagnosing clinically important PTA requiring either aspiration or drainage.…”
Section: Test Characteristics Of Ultrasound For the Diagnosis Of Peri...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Urban et al [ 4 ] supports the treatment of abscess sizes <2 cm using medical management alone. Due to resident physician and training availability, our institution has historically attempted drainage of much smaller abscesses, and we anticipated a difficult transition to endorse solely medical management for all PTAs <2 cm.…”
Section: Introductionmentioning
confidence: 97%
“…Due to resident physician and training availability, our institution has historically attempted drainage of much smaller abscesses, and we anticipated a difficult transition to endorse solely medical management for all PTAs <2 cm. To aid in this transition in management, the size cut-off for this protocol was 1.7 cm, based on the aforementioned study by Urban et al [ 4 ], where 1.69 cm was the average size of an abscess treated successfully with medical management alone.…”
Section: Introductionmentioning
confidence: 99%